2020
DOI: 10.3390/molecules25173864
|View full text |Cite
|
Sign up to set email alerts
|

A Structure-Activity Relationship Comparison of Imidazodiazepines Binding at Kappa, Mu, and Delta Opioid Receptors and the GABAA Receptor

Abstract: Analgesic and anti-inflammatory properties mediated by the κ opioid receptor (KOR) have been reported for oxadiazole imidazodiazepines. Affinities determined by radioligand competition assays of more than seventy imidazodiazepines using cell homogenates from HEK293 cells that overexpress KOR, µ opioid receptor (MOR), and δ opioid receptor (DOR) are presented. Affinities to synaptic, benzodiazepine-sensitive receptors (BZR) were determined with rat brain extract. The highest affinity for KOR was recorded for GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The kappa opioid receptors (KOR), µ and δ opioid receptors (MOR and DOR), and nociception opioid receptor (NOP) fall under the family of opioids receptors [ 81 ]. It has been reported that oxadiazole imidazodiazepines can mediate analgesic and anti-inflammatory properties mediated also by the κ opioid receptor (KOR) [ 82 ]. The binding at KOR is usually silent.…”
Section: Resultsmentioning
confidence: 99%
“…The kappa opioid receptors (KOR), µ and δ opioid receptors (MOR and DOR), and nociception opioid receptor (NOP) fall under the family of opioids receptors [ 81 ]. It has been reported that oxadiazole imidazodiazepines can mediate analgesic and anti-inflammatory properties mediated also by the κ opioid receptor (KOR) [ 82 ]. The binding at KOR is usually silent.…”
Section: Resultsmentioning
confidence: 99%
“…Classical opioid receptors can be divided into three types: μ, κ and σ. As the most widespread opioid receptors, µ receptors have been confirmed to be widely involved in analgesia and sedation as well as other processes (Li et al, 2020;Valentino and Volkow, 2018) (Figure 2). As µ receptor agonists, fentanyl analogs can bind and activate μ1 receptors and play an analgesic role.…”
Section: Opioid Receptor Hypothesismentioning
confidence: 99%
“…We can conclude that the conjugation of MIDD0301 at the carboxyl group can generate amides that retain GABA A R affinity. Other examples of MIDD0301-derived amides and esters have been reported. Furthermore, compounds like PI320 have excellent physicochemical properties, quick onset of smooth muscle relaxation, and potently alleviate AHR. PI320 can be nebulized as an aqueous solution achieving high lung concentrations and a good half-life.…”
Section: Results and Discussionmentioning
confidence: 99%